2018
DOI: 10.1038/s41467-018-04766-9
|View full text |Cite
|
Sign up to set email alerts
|

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity

Abstract: Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 34 publications
5
73
0
Order By: Relevance
“…To summarise, in meta-analyses of nearly 300,000 individuals we identified 210 loci, of which 149 were novel, underlying cardiac conduction as manifested by the electrocardiographic PR interval. Apart from confirming well-established associations in loci harbouring ion-channel genes, our findings further underscore the central importance of heart development and cytoskeletal components in atrioventricular conduction 10,12,13 . We also highlight the role of common variation at loci harboring genes underlying monogenic forms of heart disease in cardiac conduction.…”
Section: Main Textsupporting
confidence: 79%
See 1 more Smart Citation
“…To summarise, in meta-analyses of nearly 300,000 individuals we identified 210 loci, of which 149 were novel, underlying cardiac conduction as manifested by the electrocardiographic PR interval. Apart from confirming well-established associations in loci harbouring ion-channel genes, our findings further underscore the central importance of heart development and cytoskeletal components in atrioventricular conduction 10,12,13 . We also highlight the role of common variation at loci harboring genes underlying monogenic forms of heart disease in cardiac conduction.…”
Section: Main Textsupporting
confidence: 79%
“…In total, we identified missense variants in genes at 12 novel and 6 previously reported loci ( Supplementary Table 12 ). At MYH6 , a previously described locus for PR interval 6,10 , sick sinus syndrome 16 , AF and other cardiovascular traits 17 , we observed a novel predicted damaging missense variant in MYH6 (rs28711516, p.Gly56Arg). MYH6 encodes the α-heavy chain subunit of cardiac myosin.…”
Section: Main Textmentioning
confidence: 73%
“…SPSB3 is involved in degradation of the transcription factor SNAIL, which regulates the epithelialmesenchymal transition 15 , and has not been previously associated with cardiovascular traits. At MYH6, a previously described locus for PR interval 6,10 , sick sinus syndrome 16 , AF and other cardiovascular traits 17 , we observed a previously not reported predicted damaging missense variant in MYH6 (rs28711516, p. Gly56Arg). MYH6 encodes the α-heavy chain subunit of cardiac myosin.…”
Section: Resultsmentioning
confidence: 52%
“…The PR interval also serves as a risk factor for atrial fibrillation and cardiovascular mortality [1][2][3] . Prior genetic association studies have identified 64 PR interval loci [4][5][6][7][8][9][10][11][12][13] . Yet the underlying biological mechanisms of atrioventricular conduction and relationships between genetic predisposition to PR interval duration and disease are incompletely characterized.…”
mentioning
confidence: 99%
“…Recently, TTN was identified as being associated with atrial and atrioventricular electrical activity though genome-wide association study. 19 However, the relationship between TTN and AVB is illusive; the underlying genetic mechanism contributing to the third degree AVB is still not fully characterized. 1,20…”
Section: Introductionmentioning
confidence: 99%